Analisis Nilai Kemanusiaan Dalam Ludruk “Sogol Pendekar Sumur Gemuling” - Misbahul Khanif; Akhmad Fatoni (Semantik : Jurnal Riset Ilmu Pendidikan, Bahasa dan Budaya, 2025)
Ludruk "Sogol Pendekar Sumur Gemuling" is a performing art work rich in human values. In this analysis, the theme of solidarity is highlighted through the interaction of characters who support each other in facing challenges. The courage of the characters in fighting for the truth and protecting the weak illustrates the essence of human struggle in everyday life. Intelligent and meaningful dialogues lead the audience to reflect on their role in the community, as well as the importance of respecting and helping each other. In addition, the sacrifices shown by the main characters provide a deeper dimension to the understanding of human values. These sacrifices are not only physical, but also emotional, reflecting the complexity of human relationships. Through these elements, this ludruk successfully invites the audience to absorb the importance of empathy and a sense of social responsibility. Thus, "Sogol Pendekar Sumur Gemuling" is not only entertainment, but also a means of reflection on the noble values that must be upheld in community life.